The role of computer in the process of solving of mathematical problems (results of research) - Kąkol, Henryk; Ratusiński, Tadeusz (Teaching Mathematics and Computer Science, 2007)
We would like to present results of an almost two years investigations about the role computer in the process of solving of mathematical problems. In these investigations took part 35 students of the secondary school (generalists) in the age 17–19 years. Each of these students solved following problem:Find all values of the parameter m so that the functionf(x) = |mx + 1| − |2x − m| is:a) bounded,b) bounded only from the bottom,c) bounded only from above,first without a computer and next with a special computer program. We would like to show results of these researches.